2020
DOI: 10.14814/phy2.14425
|View full text |Cite
|
Sign up to set email alerts
|

The effects of clothing layers on the thermoregulatory responses to short duration babywearing in babies under 12 months old

Abstract: Carrying babies in a sling, that is, babywearing, is a popular practice among new parents. Babies are thermally vulnerable and public health bodies advise to dress them in one extra layer than the adult. However, these guidelines do not consider babywearing and it is unclear whether babies’ clothing insulation should be modified during babywearing. Here we quantified the effects of babies’ clothing layers on the thermoregulatory responses to short duration babywearing in babies under 12 months old. Nine babies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…, 2018). American Academy of Pediatrics (AAP) and World Health Organization (WHO) recommended dressing infants in “on extra layer” than adults to ensure suitable thermal protection (Filingeri et al. , 2020).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…, 2018). American Academy of Pediatrics (AAP) and World Health Organization (WHO) recommended dressing infants in “on extra layer” than adults to ensure suitable thermal protection (Filingeri et al. , 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This difference can be explained by the different metabolic heat production and the body surface area for heat loss between infants and adults (Fukazawa et al, 2009;Schlabach et al, 2018). American Academy of Pediatrics (AAP) and World Health Organization (WHO) recommended dressing infants in "on extra layer" than adults to ensure suitable thermal protection (Filingeri et al, 2020). Our findings further demonstrated that the amount of bedding for infants should be set based on month-age, and the guidance from AAP and WHO was more applicable for the younger infants.…”
Section: Recommendations For Infant Bedding Usementioning
confidence: 99%
See 2 more Smart Citations
“…In addition, dressing can also protect the body from the hot sun, insect bites, and others. So, dressing can affect a person's personal soul, both physically and spiritually (Filingeri et al, 2020;Uddin et al, 2022). From the way of dress, a person can be judged by his personality, environment and tastes.…”
Section: Introductionmentioning
confidence: 99%